(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The Municipal Savings and Credit Banks (MSCB) have become relevant in the financial market, providing easy access to credit from Small and Medium Enterprises (SMEs). Therefore, the research focuses on analyzing the level of financial sustainability of the SMEs in Peru 2010-2021. For this, the CAMEL method was used to identify the level of financial strength from the financial data available in the Superintendency of Banking and Insurance (SBI). The results reveal that the SMEs Arequipa and Huancayo lead the ranking, but the SMEs Del Santa and Paita show weakness in financial indicators such as profitability and risk of default.